Current State of the Problem of Rationalization of Schoolchildren's Nutrition - Rakhimova Durdona Zhurakulovna; Utamuradova Nigora Abdurakhmanovna (Genius Journals, 2023)
Today, the number of nutrition-related diseases is growing all over the world, especially among children, which requires increased attention to the problem. The article highlights the nutritional problems of school-age children, nutrition-related and social risk factors that affect the health of the child.
Keywords: nutrition; alimentary diseases; school-age children